PENGGUNAAN CENDAWAN MIKORIZA ARBUSKULA (CMA) UNTUK MENGENDALIKAN Fusarium oxysporum f.sp. cubense DAN NEMATODA Radopholus similis PADA TANAMAN PISANG BARANGAN (Musa Paradisiaca L.) DI RUMAH KACA - Rini Ambarwulan; lLisnawita Lisnawita; Lahmuddin Lubis Lahmuddin Lubis (Universitas Sumatera Utara, 2013)
The use of mycorrhizal arbuscula fungi (MAF) to control the Fusarium oxysporum f.sp.cubense and Radopholus similis on Barangan banana (Musa paradisiaca L.) in glasshouse.The research was to knew the effectivity of MAF in controling Fusarium wilt and R. similison Barangan Banana. The research was carried out in glasshouse of Agriculture Faculty,University of Sumatera Utara, Medan since May until December 2012. The method of thisresearch was Randomized Complete Design Non Factorial with nine treatment, namelycontrol, inoculation of MAF, inoculation of R. similis, inoculation F. oxysporum f.sp cubense,inoculation of mycorrhizal, R. similis & Foc, inoculation of Foc one week later MAF and R.similis, inoculation of R. similis one week later CMA dan Foc inoculation of MAF one weeklater Foc one week later R. similis; inoculation of MAF one week later R. similis one weeklater Foc and with three replication. The parameters are incubation period (days), diseaseincidence (%), and disease severity (%). The results showed that fastest incubation period inthe treatment M0R0F1 are 11 days and the lowest in the treatment M1R3F2, M1R2F3 are 20days. The highest percentage of disease incidence in the treatment M0R0F1 are 88.89% andthe lowest in the treatment M1R2F3 are 22.22%. The highest disease severity in the treatmentM0R0F1 are 35.56% and the lowest in the treatment M1R2F3 are 8.89%.Keywords: Mycorrhizal Arbuscula Fungi, Fusarium oxysporum f.sp cubense,Radopholus similis, banana